Sizing of standalone PV power system for telecommunication / Mohd Saifulidham Mohd Noor - Mohd Noor, Mohd Saifulidham (2014)
This thesis present the method for determining the Sizing of Standalone Photovoltaic (PV) Power System in term of sizing of PV array and battery storage for School netVSAT and Public Phone usage. The system is specifically designed to cover the power necessities of remote, isolated telecommunications facilities, and should be able to work for at least 5 years. In finding the optimal sizing of standalone PV power system, data consumption for each type of service is considered. As of other standalone PV power system, this project will generate electric power by using solar cell where the energy from the sun is converted into a flow of electrons. In ensuring the validity of the proposed method, the existing standalone PV power system is selected as a reference. The proposed method gives very close values to existing standalone PV power system. However the proposed method is better than existing one because of its simplicity and wide availability.